Highlights of Practical Applications of Agents, Multi-Agent Systems, and Sustainability - The PAAMS Collection: International Workshops of PAAMS 2015, Salamanca, Spain, June 3-4, 2015. Proceedings - Bajo, J (Springer, 2015)
This book constitutes the refereed proceedings of the workshops which complemented the 13th International Conference on Practical Applications of Agents and Multi-Agent Systems, PAAMS 2015, held in Salamanca, Spain, in June 2015. The 36 revised full papers presented were carefully reviewed and selected from 91 submissions. This volume presents the papers that have been accepted for the following workshops: Workshop on Agents and multi-agent Systems for AAL and e-HEALTH, Workshop on Agent-Based Solutions for Manufacturing and Supply Chain, Workshop on MAS for Complex Networks and Social Computation, Workshop on Intelligent Systems for Context-based Information Fusion, Workshop on Multi-agent based Applications for Smart Grids and Sustainable Energy Systems, Workshop on Multiagent System based Learning Environments, Workshop in Intelligent Human-Agent Societies.